Climate Change Adaptation Among Cassava Farmers in Okigwe Agricultural Zone of Imo State, Nigeria - Chibuzo Uzoma Izuogu; Loveday Chukwudi Njoku; Gillian C. Azuamairo; Chikerenma M. Atasie; O. O. Ekumankama (International Journal of Agriculture System, 2023)
Climate change, which exposes farmers to low productivity, crop failure and worsens food insecurity in developing nations has become a core challenge in Nigeria. These extremes have increased the vulnerability of several arable crop farmers due to inadequate mitigation strategies and restricted access to capital. This study analyzed climate change adaptation among cassava farmers in Okigwe agricultural zone of Imo State, Nigeria.  Perception of cassava farmers towards climate change, their adaptation strategies and challenges to climate change adaptation and determinant of farmers’ adaptation to climate change were the main objectives. A multi-stage random sampling procedure was used in selecting one hundred and twenty respondents for the study. Data were collected using structured questionnaire and analyzed with percentages, mean and Chi square. Results showed that the mean age of the respondents was 47 years while 78.30% of them had formal education.  The main adaptation strategies included planting on mounds (20%), diversification to non-farm activities (15%) and planting of improved varieties (14%). Cassava farmers in the study area perceived climate change as increase in heat waves (x̅=2.26), rainfall (x̅=2.76) and drought (x̅=2.35). The major challenges to adaptation were unsatisfactory weather reports (89.5%), lack of funds (82.4%) and inadequate extension contact (81.2%). Extension contacts and access to credit were the most significant determinants of utilization of climate change adaptation strategies. The study concludes that respondents are aware of climate change with diverse adaptation strategies and recommends that government and agricultural development agencies should integrate the determinant of climate change adaptation and mitigation into policies and programs relating to climate change resilience.  It also recommends that the availability of climate change information in real time, mobilization of more extension workers and provision of funds to improve the capacity of cassava farmers for climate change resilience should be prioritized